P289 Syphilis testing at ANC in kenya: dual testing as a game changer towards eMTCT. (14th July 2019) - Mati, Carolyne; Ngugi, Catherine; Wafula, Rose; Agwata, Bob; Bartilol, Kigen
Abstract : Background: The ANC guidelines advocate every woman in the ANC to get tested of both HIV and Syphilis in Kenya. Despite these recommendations, the level of coverage of Syphilis testing has been low, as a result woman are supported to protect their babies from HIV, only for them to lose their babies due to pregnancy loses and babies dying from congenital syphilis. In addition, the HIV negative pregnant women who have undiagnosed and untreated STIs have an increased risk of acquiring HIV. In July 2017, Kenya launched an elimination of MTCT of HIV and Syphilis Strategic Framework 2016–2022. This paved way to the investment and introduction of HIV & Syphilis Dual test kit use in ANC from March 2018. We thus, sought to know the extent of adherence to syphilis testing among pregnant women at ANC. Methods: The operational research was a retrospective analysis of reported data from October to December 2016, 2017 and 2018. The data used was sourced from DHIS2.Upon assessment of completeness tabulation was done, and summary statistics obtained. Results: A total of 289, 875 women who visited 1stANC in October to December 2016, 277, 196 (95.6%) were tested for HIV and12, 161 (4.3%) tested HIV positive, the proportion that was screened for syphilis was 211, 546 (72.9%) women and out of those, 2, 396 (1.1%) women tested positive for syphilis. In October to December 2017, a total of 336, 512 women visited ANC, 306, 573 (91.1%) women tested for HIV and 15, 056 (4.9%) turned positive while 262, 567 (78%) were tested for syphilis and 3, 072 (1.2%) turned positive. In 2018 same quarter, 336, 687 women visited ANC, 298, 598 (88.9%) were tested for HIV, 16, 5805 (6%) turned positive while 307, 842 (91%) tested for syphilis and 3, 464 (1.1%) tested positive of syphilis. Thus, for the first time ever in Kenya syphilis testing has caught up with HIV testing at 1 st ANC. This is an improvement to 91% from 73% which is critical for achievements of the country's eMTCT targets. Conclusion: Syphilis not only result s in intrauterine fetal demise, but also facilitates HIV acquisition and impede progress towards eMTCT. Kenya's commitment to reduce MTCT of HIV and Syphilis to below 5% by 2019 requires our country to improve Syphilis screening/testing. To increase syphilis testing, the use of dual testing kits at ANC should be used widely and every woman at ANC should be encouraged and educated on the importance of syphilis test. Disclosure: No significant relationships.